Correction: 9, 9′-Anthryl-anthroxyl radicals: strategic stabilization of highly reactive phenoxyl radicals. Issue 24 (2nd March 2015) - Aotake, Tatsuya; Suzuki, Mitsuharu; Aratani, Naoki; Yuasa, Junpei; Kuzuhara, Daiki; Hayashi, Hironobu; Nakano, Haruyuki; Kawai, Tsuyoshi; Wu, Jishan; Yamada, Hiroko
Abstract : Correction for '9, 9′-Anthryl-anthroxyl radicals: strategic stabilization of highly reactive phenoxyl radicals' by Tatsuya Aotake et al., Chem. Commun., 2015, DOI: ; Web:10.1039/c4cc10104a .